La experiencia de sufrir una insuficiencia cardiaca crónica. Un padecimiento que acerca a la muerte (2011)
ABSTRACT: To understand how people with Chronic heart failure (CHF), perceive, understand, and answer to the manifestations and effects of the disease. Methodology. Grounded theory qualitative research. Data was gotten from semi-structured interviews to 13 people, men and women between 40 and 85 years of age, from different educational and socioeconomic levels. The research was carried out in Medellin (Colombia) in 2007. Results. Interviewers perceive death as a close fact, this idea is reassured with the restrictions the disease imposes. This situation makes them establish important changes in their life style; their relationships with other people, and their environment, allowing them improve their health, control the disease, and improve survival. Conclusion. Participants accept CHF through a process, in which, when feeling close to death, change their way of coping with the disease.